Targeting intestinal inflammation using locked nucleic acids delivered via lipid nanoparticles - Shahd Qassem; Gonna Somu Naidu; Meir Goldsmith; Dor Breier; Riccardo Rampado; Srinivas Ramishetti; Michael Keller; Felix Schumacher; Kara G. Lassen; Leilah Otikovs; Roman Kamyshinsky; Inbal Hazan-Halevy; et al. (Nature Communications)
Abstract Locked nucleic acids are a third-generation antisense oligonucleotides with high binding affinity. A major limitation is the high dosages they require to achieve efficacy which may induce unwanted adverse effects. Here, we report the use of Lipid-based nanoparticles to deliver locked nucleic acids for treating intestinal inflammation in mice. Eight formulations with novel ionizable lipids were screened for stability and toxicity. Particles were loaded with splice-switcher sequence, enabling a precise assessment of potency in vitro. Three lead candidates were tested in vivo, demonstrating a 30-fold dose reduction compared to the unformulated oligonucleotides. The most potent formulation, encapsulating a sequence against Tumor necrosis factor alpha, was evaluated in a mouse model of colitis. Treatment reduced disease severity and inflammatory cytokines, with good safety. These findings support the use of lipid nanoparticles for the precise delivery of locked nucleic acids and highlight their promise for future therapies.